Role of preoperative carbohydrate loading for prevention of perioperative ketoacidosis in elective cesarean delivery - Ankita Sharma; Udeyana Singh; Gurpreeti Kaur; Anju Grewal; Sahil Maingi; Swati Tidyal (Wolters Kluwer Medknow Publications, 2024)
Background and Aims: Starvation of long duration during third trimester of pregnancy is undesirable as it is associated with accelerated fasting leading to hypoglycemia, raised plasma free fatty acid (FFA) levels, and increased plasma/urinary ketones. Carbohydrate (CHO)-rich drinks given preoperatively may ameliorate these deleterious effects. The enhanced recovery after surgery (ERAS) guidelines for perioperative care recommend that oral CHO fluid supplementation 2 h before cesarean delivery may be offered to nondiabetic pregnant women. The aim of the study was to evaluate the role of preoperative oral CHO loading for the prevention of perioperative ketoacidosis in elective cesarean deliveries. Material and Methods: One hundred and twenty American Society of Anesthesiologists (ASA) II/III parturients undergoing elective cesarean section under subarachnoid block (SAB) were divided into two groups of 60 each after they gave written informed consent. Group A parturients received 400 ml of filtered water 2 h before surgery. Group B parturients received 400 ml of nonparticulate CHO drink 2 h before surgery. The primary outcome was the incidence of ketonuria studied by the dipstick method. Secondary outcomes included hunger and thirst scores, anxiety score, dominant hand grip strength, and the quality of recovery score. Results: The urine ketone levels were positive (+1) in 8.3% parturients in group A and 1.7% parturients in the CHO group (P value- 0.094). The hunger and thirst scores as well as the modified Beck's anxiety scores were significantly lower in the CHO group (P value- 0.002). Dominant hand grip strength was preserved in both the groups (P value- 0.827). The quality of recovery score was significantly improved in the CHO group (P value- 0.002). No serious adverse effects were noted in either group. Conclusion: Oral CHO drink is safe when administered 2 h before uncomplicated elective cesarean deliveries. It may have a positive influence on a wide range of perioperative markers of clinical outcome.